TASK-TECHNOLOGY FIT IN ACCOUNTING INFORMATION SYSTEMS: IMPACT ON COST MANAGEMENT EFFICIENCY IN MALAYSIAN HIGHER EDUCATION - Shuhidan, Shazalina Mohamed; Mohamed, Intan Salwani; Awang, Yunita; Mat Dangi, Mohamad Ridhuan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Malaysian educational initiatives, including the National Higher Education Strategic Plan and the Malaysia Education Blueprint, highlight the importance of Accounting Information Systems (AIS) in improving cost management efficiency in Higher Education Institutions (HEIs). Despite widespread AIS implementation, many managers remain unaware of its benefits, limiting effective decision-making. Consequently, underutilization leads to insufficient information, suboptimal decisions, and challenges in achieving institutional objectives. This study investigates the role of AIS in enhancing cost management decision-making in HEIs by examining factors influencing Task Technology Fit (TTF), the relationship between TTF and cost management efficiency, and the moderating effect of managers’ work experience. Data were collected from 106 managers across 11 Malaysian public HEIs and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings indicate variations in managers’ perceptions of AIS TTF, particularly in cost management decision-making. Information quality and system quality were identified as key determinants of TTF, with task variability also significantly influenced TTF. AIS was most effective when managers perceive it as useful and had relevant institutional experience. These findings provide insights for HEI stakeholders to enhance AIS implementation and inform the application of TTF theory. Future research could examine whether these findings generalize to private higher education institutions.